Optimization of Power Cable Layout Scheme for Point Absorption Wave Energy Converters. Issue 1 (1st April 2022) - Han, Guoxin; Bao, Xingxian
Abstract: This paper studies the power cable of the point absorption wave energy converters (WECs). As bearing the cyclic loads induced by WECs motion, waves and ocean currents, cable is prone to damage and failure. Therefore, it is necessary to optimize the design of the power cable to improve its performances and ensure the service safety of the WECs system. The idea of setting buoyancy modules on different positions of the power cable is proposed in this paper. The length and weight of the power cable and the length and position of buoyancy modules are considered to optimize the design of the power cable in the numerical simulation. The optimal design is evaluated based on the maximum effective tension and curvature of the power cable and the captured power of the WEC. The schemes of the cable with buoyancy modules and without buoyancy modules are compared based on the maximum effective tension and curvature of the power cable and the captured power of the WEC. The results show that the cable performance is significantly improved after setting the buoyancy modules, but the improvement for the captured power of the WEC is little.